Interaction in virtual learning environments: an analysis of two discussion forums - DOI: 10.3395/reciis.v3i2.219en - Josué Laguardia; Rejane Ramos Machado; Eliana Coutinho (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
The role of interaction in constructing knowledge in discussion forums in virtual learning environments (VLE) is often supported by students' reports regarding their experiences in such forums. This paper aims to describe the interaction and knowledge construction patterns in an online forum, based on the social network theory and on cognitive levels of increasing complexity. The classification of cognitive levels (SOLO taxonomy) was used as a theoretical framework when analyzing the data. We noticed that the number of messages posted, sent and received varied among the forums, which resulted in variations in centrality measures of those forums. The tutor participated actively in forum I. He interacted with the students throughout the activity. Such activity was restricted in forum II, where the tutor was limited to posting the initial and closing messages of the forum. This has not resulted in significant changes in student's interaction, unlike scientific literature which associates greater participation by the tutor with greater interaction between participants.